Analisis Risiko dalam Pengambilan Keputusan Administratif di Sekolah - Elshi Aidira, Della; Irsyad; Setiawati, Merika (CV. ITTC INDONESIA, 2025)
This article discusses the importance of applying risk analysis to the administrative decision-making process in educational institutions. In education, every managerial decision carries potential risks that can impact service quality, resource efficiency, and the sustainability of school activities. Through a risk analysis approach, decision-makers can assess the likelihood and impact of an event, thus making policies more accurate, measurable, and problem-prevention oriented.